Analisis Nilai Moral dalam Cerita Rakyat "Dua Orang Sunan Beradu Jago" - Nova Khoirun Nisa; Enjelina Zahwa Artha Mevia; Ula Aulia As Sanusi (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This research aims to analyze the intrinsic elements and moral values contained in the folklore entitled "Dua Orang Sunan Beradu Jago". Folklore as part of intangible cultural heritage has a wealth of oral literature that is loaded with life messages and moral teachings. In this research using qualitative descriptive methods with content analysis techniques, which is to examine story fragments as the main data source. The intrinsic elements analyzed include themes, characters and plots, plots, settings, points of view, and mandates. While the moral values studied include aspects of human relationships with God, fellow human beings, and the environment. The research results show that this folk tale contains the theme of competition wrapped in religious nuances and local wisdom. The main character, namely two sunan people, is described as a highly educated figure but has their own ego. The story develops through an advanced plot that depicts a power struggle as a symbol of spiritual competition and power. The setting used highlights the cultural atmosphere of the Javanese coastal people. Moral values that can be taken include the importance of humility, staying away from pride, and putting common interests above personal ego. This research is expected to enrich the study of oral literature and become a means of preserving noble values in local culture.